Da mandinga à macumba: a trajetória do livro de São Cipriano no Brasil - Barreto, Inês Teixeira (2022)
The Book of Saint Cyprian is a Portuguese book on magic that compiles spells, instructions for the divination of the future, exorcism procedures and treasure disenchantment. It has a strong influence from medieval European grimoires, but it also absorbed other aspects of Portuguese Catholicism. From the contacts between Brazil and Portugal, which began with colonial domination and lasted through economic exchanges and migratory processes during the Empire and the Republic, the Book arrived in the country and added to magical-religious imagery full of influences by Iberian, African and Amerindian cultures. The present work investigates the trajectory of this book from Portugal to its popularization in Brazil in the 20th century, covering the path of many editions in the publishing market, pointing out the modifications and contributions created from Brazilian elements that added to the inherited content from Portugal. The research also brings case studies of supposed readers and their magical-religious practices with a Catholic background but influenced by Iberian and Afro-Amerindian religiosities. The present research uses, as main sources, editions of The Book of Saint Cyprian, advertisements published in Brazilian newspapers and magazines between 1870 to 1970, as well as news of police persecution of sorcerers, macumbeiros and healers. Books by folklorists, ethnologists and intellectuals were also used as secondary sources. The intention is to demonstrate how a religious cultural element from the Iberian Peninsula became part of Brazilian religious imaginary, given the plurality of Brazil’s cultural and ethnic background. This process of encounter and modification that can be called mestizaje, a positive synonymous for miscegenation, according to the concept developed by Serge Grunzinsky